Swirl-switching phenomenon in turbulent flow through toroidal pipes - Noorani, Azad; Schlatter, Philipp (9th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2015, 2015)
Direct numerical simulations (DNS) are performed to investigate turbulent flows in toroidal pipes with mild and strong curvature. By means of proper orthogonal decomposition (POD), dominant structures in the flow field are identified. The most energetic structures in the strongly curved pipes (κ = 0.1 and κ = 0.3) are very similar in both configurations studied here. These modes (shape and frequency) also match the coherent structures responsible for swirl switching phenomenon found earlier in experimental and numerical studies of turbulent flow in spatially developing 90° bends with which the current results are compared. The observed swirl switching in toroidal pipes, which is isolated from any upstream and separation conditions, may challenge the current hyphothesis regarding the origin of swirl switching mechanism.
CRIS-Team Scopus Importer:2023-03-21